Privacy on the ground : driving corporate behavior in the United States and Europe - Bamberger, Kenneth A., 1968- author.; Mulligan, Deirdre K., author. (Cambridge, Massachusetts : The MIT Press, 2015)
Paradoxes of privacy on the books and on the ground -- Literature, framework, and methodology -- Background law -- Empirical findings--United States -- Empirical findings--Germany -- Empirical findings--Spain -- Empirical findings--France -- Empirical findings--United Kingdom -- Identifying best practices : the promise of U.S. and German privacy operationalization -- The U.S. privacy field -- The development of the German privacy field -- Catalyzing robust corporate privacy practices : bringing the outside in -- Moving forward.